Composable security of CV-MDI-QKD with secret key rate and data processing - Panagiotis Papanastasiou; Alexander G. Mountogiannakis; Stefano Pirandola (Scientific Reports, 2023)
Abstract We provide a rigorous security proof of continuous-variable measurement-device-independent quantum key distribution which incorporates finite-size effects and composable terms. In order to use realistic and optimized parameters and be able to derive results close to experimental expectations, we run protocol simulations supported by a Python library, including all the protocol operations, from simulating the quantum communication till the extraction of the final key.